WPŁYW PRAWA BIZANTYJSKIEGO NA OPIEKĘ W RUSKIEJ PRAWDZIE I W I STATUCIE LITEWSKIM - Godek, Sławomir (Zeszyty Prawnicze, 2017)
The influence of Byzantine law on tutelage in the Russkaya Pravda and th e First Lithuanian Statute The article is dedicated to the influence that Byzantine law had on Russian law (with a particular focus on the Russkaya Pravda) and on the First Lithuanian Statute of 1529. The paper analyses the main channels of influence that Byzantine law had on the ancient Russian law. It happened primarily through intensive trading and political contacts between Kiev and the Byzantine Empire. Such contacts, without any doubt, were established as early as the first half of the 10th century. An important factor in the influence Byzantine law exerted on Russian law was constituted by treaties (known as „dogovory”) concluded between these states in the years 907, 911, 944, and 971. The influence of Byzantine law in Rus intensified especially after the Kievan princes adopted Christianity in its Greek tradition in 988. At that time, Byzantine law codes spread across Rus; an important role in their spreading was played by the so-called Kormchie Knigi, which contained the norms of church and secular law. The codes were bound to influence legal practice, especially in the field of family, guardianship and inheritance law, which traditionally lay within the jurisdiction of ecclesiastical courts. At the same time, princes significantly intensified their legislative activity. The acts of the Kievan and Novgorod princes are inspired by the solutions adopted in Greek law, and contain many references to this law. The influence also spread onto the Russkaya Pravda (Russian Justice), especially in its later version. All in all, the influence of Byzantine law in Rus was quite significant, which fostered the development of Russian law. It mostly affected private law and procedural law, but also, to a limited extent, criminal law. In the field of private law, the strongest influence of Greek law was felt in marriage, guardianship and family law. The provisions o f the Russkaya Pravda with respect to guardianship were modeled on the respective regulations of the codes of Byzantine law - the Ecloga and the Procheiron. The Russian code defined the position of the widow in a way reminiscent of Byzantine law - after the husband's death she was the continuer of the previous family arrangement; her rights to family property (of which she could freely dispose) and relations with children were also defined in a similar manner. Similarities can also be discerned in the regulations on the remarriage of widows, in particular, the legal consequences of this act: remarriage resulted in the loss of the right of custody over children in favor of the husband’s relatives. These provisions of the Russkaya Pravda in the field of guardianship law certainly exerted some influence on the development of the legal institution of guardianship at the time when Russian lands were included into the Lithuanian state. This was reflected in privileges granted to the Lithuanian szlachta (gentry), which reiterated the principles known from the Russkaya Pravda. This, in particular, applies to the privileges that defined the legal position of a widow (privilege of 1447). The same principles also constituted the grounds of verdicts adopted by Grand Duke’s court in cases from the field of guardianship law. With the passage of time, a significant body of experience was gathered, which laid the foundations for the respective provisions of the First Lithuanian Statute. The provisions of the Statute that regulated widows’ guardianship over children (Statute I, VI, 6) show a kinship with the provisions of the Russkaya Pravda and, through it, with the Ecloga and the Procheiron. It seems, therefore, that there was a substantial flow of ideas and readymade legal structures between Byzantine law, based on the principles of the ancient Roman law, and Russian law, whose output was, in its turn, used by the Lithuanian legislature.